Disseminated Bartonella henselae disease mimicking Langerhans' cell histiocytosis. Issue 4 (17th December 2018) - Apsemidou, Athanasia; Rauwolf, Kerstin; Tragiannidis, Athanasios; Brentrup, Angela; Schiborr, Manfred; Becker, Karsten; Ahlmann, Martina; Groll, Andreas H.
Abstract: Bartonella henselae, the causative agent of cat‐scratch disease, has been recognized to be responsible for a broad range of clinical syndromes. We report the case of a patient with disseminated B. henselae infection mimicking Langerhans cell histiocytosis at presentation and its successful management with neurosurgery, prolonged antibacterial therapy, and observation.